Optimized fosfomycin regimens for treating carbapenem‐resistant Acinetobacter baumannii in critically ill patients with varying degrees of renal function - Nattapong Tidwong; Anan Chanruang; Suthanya Chupradit; Suzanne L. Parker; Pannee Leelawattanachai; Poramed Winichakoon; Baralee Punyawudho (Clinical and Translational Science)
Abstract Fosfomycin has been used to treat carbapenem‐resistant Acinetobacter baumannii (CRAB) infections. However, there is insufficient information on dosage adjustment among critically ill patients with renal impairment. This study aims to evaluate the attainment of PK/PD targets for different dosage regimens of CRAB treatment in critically ill patients based on their renal function. Monte Carlo simulations were conducted to assess the probability of achieving time above the minimum inhibitory concentration (T > MIC) of 80% and 100% and to determine the cumulative fraction response (CFR) against institutional MICs. Our results demonstrated that administering fosfomycin 20–24 g/day to individuals with normal renal function (CrCl ≥60 mL/min) achieved the target at a MIC of ≤64 and ≤32 μg/mL during the first 24 h of treatment and at steady state, respectively. Notably, those with renal impairment achieved higher MIC values at a steady state despite dosage reduction. None of the regimens reached the target CFR. Our study suggested that administering fosfomycin at least 20 g/day to those with normal renal function provides sufficient exposure throughout the treatment course when the MIC value is ≤32 μg/mL. Less aggressive dosing regimens are advisable for patients with renal impairment. Additional clinical studies are necessary to verify our suggestions.